Actitud laboral del personal administrativo y satisfacción del usuario en entidades gubernamentales - Cotrado, Sheylla (Instituto Universitario de Innovación Ciencia y Tecnología Inudi Perú, 2022)
This book is an adaptation of a research presented at the Andean University of Cusco whose objective was to determine the work attitude of administrative staff and user satisfaction. Which allowed to propose a plan to improve the quality of service of the Provincial Municipality of La Convention Quillabamba Cusco 2019. In the investigation the hypothesis was raised: the relationship that exists between work attitude of the administrative staff and user satisfaction of the Provincial Municipality of the Quillabamba Cusco 2019 Convention. It is positive, the more positive appreciation the methodology that was assumed is the analytical deductive corresponding to: Type: cross-sectional research, Level: Descriptive-correlational, Design: M = Ox r Oy. Where: M = Sample O = Observation x = positive appreciation of 168 administrative services of the municipality and user satisfaction of a population: 9745 users whose sample is 347 users. The final conclusion allowed to explain the connection of the work attitude of the administrative staff and user satisfaction of the Provincial Municipality of Quillabamba - Cusco 2019